The Structure of the Latin II Examination in the new P.A.U.: towards a Harmonized Model - Montañés Gallardo, Agustín (Avances en Supervisión Educativa, 2025)
This academic year 2024/25, Spain has held its first university entrance exam since the LOMLOE came into force. The recent publication of the regulations governing this exam and the need to adapt its model to the new legal framework have highlighted the convenience of agreeing on common criteria for its design. In this article, I therefore propose to analyse the Latin exam models recently published in all university districts, focusing on their similarities and differences, as well as their adaptation to the current curricula for the subject, and concluding with some reflections and proposals on possible changes that could be introduced in the coming years.